Determination of Diagnostic Reference Level (DRL) in Non-Contrast and Contrast Thorax CT Scan Examinations at Bali Mandara Regional Hospital - Ni Luh Emy Pramitha; Gusti Ngurah Sutapa; Ni Luh Putu Trisnawati; Ni Nyoman Ratini; Hery Suyanto; Winardi Tjahyo Baskoro (Jurnal Penelitian Pendidikan IPA, 2025)
A study has been conducted to determine the Diagnostic Reference Level (DRL) in non-contrast and contrast chest CT scan examinations at Bali Mandara Hospital. The study was conducted at the Radiology Installation of Bali Mandara Hospital using dose reports from non-contrast and contrast chest CT Scan examinations with data obtained including age, gender, kV, mAs, slice thick, time rotation, Pitch, as patient information and protocols used in the examination and dose information in the form of CTDIvol and DLP. This study aims to determine the local DRL value against the national DRL value. The method used to determine the DRL value in this study is by collecting data in the form of recording and documenting the dose report of CT Scan examination patients, with the data for each examination being as many as 30. From the recorded data, the CTDIvol and DLP values are used to find the DRL value by sorting it from the smallest to the largest value and then calculating the 3rd quartile as a determinant of the local DRL. The interpolation method is also used to consider the position of the 3rd quartile so that it is at a decimal value. From the research results, the CTDIvol value for non-contrast thorax examination was 6.43 mGy, and the DLP value was 293.08 mGy.cm. Meanwhile, in contrast to the thorax examination, the CTDIvol value was 6.14 mGy, and the DLP value was 852.57 mGy.cm. Furthermore, a statistical analysis was carried out in the form of a one-way t-test using SPSS software, which was used to compare the DRL values of both CTDIvol and DLP non-contrast and contrast thorax examinations with the standard values set by BAPETEN 2021 as a reference used in Indonesia. Based on the results of the analysis with a one-way t-test, it can be seen that the DRL values for non-contrast thorax examinations (DRL CTDIvol and DLP) and contrast examinations (DRL CTDIvol) do not exceed the standards set by BAPETEN. However, in the contrast thorax CT Scan examination, the DRL DLP value exceeded the standard value set by BAPETEN, so dose optimization was needed by re-evaluating the protocol implemented at Bali Mandara Hospital.